2015
DOI: 10.1007/s13277-015-3885-1
|View full text |Cite
|
Sign up to set email alerts
|

Immature myeloid cells and tolerogenic cytokine profile in lung adenocarcinoma metastatic lymph nodes assessed by endobronchial ultrasound

Abstract: In lung cancer, the immune cell compartment of tumor-draining lymph nodes (TDLNs) dictate the response against tumors. This response is predominantly triggered by myeloid antigen-presenting cells (mAPCs) that capture antigens and, if matured, prime anti-tumor-specific T cell populations. However, the clinical role of mAPCs infiltrated in TDLN from lung cancer patients is poorly understood. The purpose of this study was to study mAPCs in TDLN from lung adenocarcinoma patients, in comparison to individuals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…IL-12, which is an important regulator of the immune response, has various anti-tumoral effects (Airoldi et al, 2009;D'Amico et al, 2012). IL-12 is a useful predictive and prognostic marker for patients with lung adenocarcinoma (Bugalho et al, 2016). Larruskain et al (2012) found that the IL-12 microsatellite was the least polymorphic with 7 alleles in OPA.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12, which is an important regulator of the immune response, has various anti-tumoral effects (Airoldi et al, 2009;D'Amico et al, 2012). IL-12 is a useful predictive and prognostic marker for patients with lung adenocarcinoma (Bugalho et al, 2016). Larruskain et al (2012) found that the IL-12 microsatellite was the least polymorphic with 7 alleles in OPA.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, clinically and/or pathologically involved lymph nodes can be tolerogenic and thus promote local and systemic immune suppression. 74,75 The robust overall survival benefit reported in PACIFIC (NCT02125461) with the addition of durvalumab was preceded by comprehensive concurrent chemoradiation targeting the primary tumor and locoregional nodal metastases. 76 Thus, reduction in tumor burden and relief of immune suppression afforded by concurrent chemoradiation may also augment immunogenicity.…”
Section: Tumor Burden As a Framework To Understand Radiation-induced mentioning
confidence: 99%